Contaminación por residuos sólidos municipales y la percepción del poblador del asentamiento humano Santa Rosa, San Juan Bautista, 2021 - Rengifo Perez, Jimmy Scot (2022)
The present work of thesis was developed in the Santa Rosa Human Settlement situated at the km 4 on the left side of the highway Santo Tomas, the evaluation was realized during the months of November 2021 to March 2022, and it had had as objective evaluated the perception of the rural villager of the Santa Rosa Human Settlement and its relation with the environmental problematic of the municipal solid waste, also, characterizer to the population in study into the aspects of knowledge, awareness and environmental attitude, and evaluated its knowledges about the management in the origin of the municipal solid waste; whit the propose of to know about the environmental problematic of the solid waste in its environment. Therefore, the present work of thesis pretends generate information from the perception of the rural villager about the municipal solid waste in the Santa Rosa Human Settlement, through the application of a survey format which covers the aspects of knowledge, awareness and management of municipal solid waste, and propose a proposal for better management, segregation and disposal, with the aim of making residents aware of the environmental problematic that represented the generation of municipal solid waste, promoting reuse and recycling, in order to achieve an environmental balance and improve the quality of life of the rural villager of the Santa Rosa Human Settlement.